Peningkatan Kapasitas Warga Dusun Tumpangrejo, Ngenep, Karangploso, Malang, Melalui Pelatihan Lampu Penerangan Jalan Umum Tenaga Surya - Bambang Minto Basuki (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service activity aims to increase the capacity of residents of Tumpangrejo Hamlet, Ngenep Village, Karangploso District, Malang Regency through training in the manufacture and use of solar-powered lamps. The main problem faced by residents is limited access to electricity in some areas, especially in remote areas not yet covered by the PLN electricity network. Furthermore, there is a lack of knowledge about environmentally friendly renewable energy technology and its potential use in daily life. The activity method begins with socialization about solar energy, where residents are given an understanding of the basic principles and benefits of solar energy as an environmentally friendly alternative energy source. Then, practical training is conducted on assembling solar-powered lamp components, which includes installing solar panels, batteries, and LEDs. During the training, participants are guided to understand each stage of the assembly process and the importance of maintaining the equipment to ensure its long-lasting and optimal function. Technical assistance is also provided after the training to ensure residents can apply the skills learned in their daily lives. Participants are encouraged to assemble and maintain solar-powered lamps independently, so they do not solely rely on external parties for maintenance. The results of this activity demonstrated an increase in residents' knowledge and skills in understanding the concept of solar energy, as well as their ability to independently assemble and maintain solar-powered lamps. Furthermore, residents began utilizing solar-powered lamps for street and household lighting. This reduced reliance on conventional electricity sources, which are often limited and expensive. This activity is expected to become a model for community empowerment based on appropriate technology in rural areas, improving their quality of life through the sustainable use of available natural resources.